Brian Moeran: A Japanese Advertising Agency. An Anthropology of Media and Market - Hansen, Sune Olofsson (Tidsskriftet Antropologi, 1999)
An Anthropology of Media and Market. Anmeldes af Sune Olofsson Hansen